2015
DOI: 10.12968/ijpn.2015.21.3.109
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with patients and their families about palliative and end-of-life care: comfort and educational needs of nurses

Abstract: Introduction Effectively discussing palliative care with patients and families requires knowledge and skill. The purpose of this study was to determine perceived needs of inpatient nurses for communicating with patients and families about palliative and end of life care. Method A non-experimental design was utilized. Sixty inpatient nurses completed the End of Life Professional Caregiver survey. Results Effects for years of experience and unit were found [F(9,131.57)=2.22, p=0.0246; Wilk's Λ=0.709 and F(6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 12 publications
6
48
1
14
Order By: Relevance
“…Professional intra-and inter-relationships and teamwork in palliative care were often based on shared trust and nurses working in home-care perceived the value of teamwork more than nurses working in hospices (Maurits, de Veer, van der Hoek, & Franck, 2015;Moir, Roberts, Martz, Perry, & Tivis, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Professional intra-and inter-relationships and teamwork in palliative care were often based on shared trust and nurses working in home-care perceived the value of teamwork more than nurses working in hospices (Maurits, de Veer, van der Hoek, & Franck, 2015;Moir, Roberts, Martz, Perry, & Tivis, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that years of nursing experience is positively associated with comfort in communicating about end of life, one of the transition points in a goals-of-care discussion (Moir, Roberts, Martz, Perry, & Tivis, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…We highlight the need to train ICU nurses on coping with the end of life, developing abilities to support patients and family members who are living through terminality (20) . The success of the work depends on the training of healthcare providers (21) . Besides that, we also highlight the importance of establishing and following directives and consensual assistance planning for end-of-life care, involving team members, patients requests (if they have autonomy and conditions for this), and family members for the assistance to be less aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the longer the time of employment of the nurse, the better he/she is prepared for dealing with matters related to end-of-life care (21,23) . Likewise, the more involved with the patient and family, the more significant the death becomes to the professional, and death predictable situations were less traumatic (24) .…”
Section: At the Beginning The Assistance Is For The Patient To Livementioning
confidence: 99%